Knowledge and Attitude Regarding Non-Invasive Prenatal Testing (NIPT) among Women: A Cross-Sectional Study in Saudi Arabia - Nedaa Mohammed Bahkali; Ghaida Abdullah Eissa; Abdulaziz Mohammed Bashar Shaheen; Abdullah Mohammed Sanedi; Duaa Mohammed Bahkali (Clinical and Experimental Obstetrics & Gynecology)
Background: The most prevalent type of inherited intellectual disability worldwide is Down syndrome. Prenatal testing can determine the possibility of a pregnant woman giving birth to an infant with Down’s. Many invasive interventions help with early diagnosis of Down’s. Although high-risk pregnancies should be offered invasive prenatal diagnosis, the International Society for Prenatal Diagnosis encourages non-invasive prenatal screening testing (NIPT) as a primary screening test for all pregnant women, regardless of risk. The present study aimed to determine the knowledge and attitude regarding NIPT among Saudi Arabian women. Methods: This cross-sectional study involving 1028 participants living in Saudi Arabia was conducted from February to March 2023, using a re-designed questionnaire shared among women with pregnancy history. The questionnaire assessed their knowledge, attitudes, and beliefs regarding NIPT. Results: Only 14.8% of our respondents had undergone NIPT; the most common indication was a recommendation from their healthcare provider (41.7%). About 3.4% of the respondents had given birth to a child with Down syndrome, and 22% had relatives with chromosomal abnormalities or genetic diseases. Surprisingly, only 22.3% of the respondents had previously heard about NIPT. The mean knowledge score about NIPT was 2.82 ± 1.89. The mean knowledge score was found to be significantly higher among females who had undergone NIPT, were aged <30, and had high school education. Conclusions: Most Saudi Arabian women have poor knowledge about NIPT and a positive attitude toward it. Thus, the suggestion is to raise awareness about NIPT use, indications, prices, and possible complications.